AGAMOUS-LIKE67 Cooperates with the Histone Mark Reader EBS to Modulate Seed Germination under High Temperature. Issue 1 (23rd June 2020) - Li, Ping; Zhang, Qili; He, Danni; Zhou, Yun; Ni, Huanhuan; Tian, Dagang; Chang, Guanxiao; Jing, Yanjun; Lin, Rongcheng; Huang, Jinling; Hu, Xiangyang
Abstract: A MADS-box protein recruits a histone mark reader to modulate thermoinhibition of seed germination by epigenetically regulating abscisic acid and gibberellic acid metabolism. Abstract: Seed germination is a vital developmental process that is tightly controlled by environmental signals, ensuring germination under favorable conditions. High temperature (HT) suppresses seed germination. This process, known as thermoinhibition, is achieved by activating abscisic acid and inhibiting gibberellic acid biosynthesis. The zinc-finger protein SOMNUS (SOM) participates in thermoinhibition of seed germination by altering gibberellic acid/abscisic acid metabolism, but the underlying regulatory mechanism is poorly understood. In this study, we report that SOM binds to its own promoter and activates its own expression in Arabidopsis ( Arabidopsis thaliana ) and identify the MADS-box transcription factor AGAMOUS-LIKE67 (AGL67) as a critical player in SOM function, based on its ability to recognize CArG-boxes within the SOM promoter and mediate the trans-activation of SOM under HTs. In addition, AGL67 recruits the histone mark reader EARLY BOLTING IN SHORT DAY (EBS), which recognizes H3K4me3 at SOM chromatin. In response to HTs, AGL67 and EBS are highly enriched around the SOM promoter. The AGL67-EBS complex is also necessary for histone H4K5 acetylation, which activates SOM expression, ultimately inhibiting seed germination. Taken together, our results reveal an essential mechanism in which AGL67 cooperates with the histone mark reader EBS, which bridges the process of H3K4me3 recognition with H4K5 acetylation, thereby epigenetically activating SOM expression to suppress seed germination under HT stress.